2008
DOI: 10.1093/europace/eun094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cryoablation catheter size on success rates in the treatment of atrioventricular nodal re-entry tachycardia in 160 patients with long-term follow-up

Abstract: Cryoablation is a safe and efficacious treatment for AVNRT. Complete slow pathway block is associated with long-term success, together with the use of the larger 6 mm cryocatheter. There is always a risk of heart block with radiofrequency ablation, although this experience confirms previous findings that the risk with Cryo is zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 13 publications
2
51
0
2
Order By: Relevance
“…Despite the comparable acute success rate, SP ablation by cryoenergy is still associated with a higher rate of arrhythmia recurrence than is SP ablation by RF 2,3 ; long-term success, however, may improve with increasing experience, while the high safety profile is maintained. 6 As previous studies [12][13][14] reported higher long-term success rate with use of the 6-mm rather than the 4-mm-tip ablation catheter, we chose to use the former for all patients. In fact, a larger tip catheter is expected to create wider lesions, which are likely to be associated with less recurrences at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the comparable acute success rate, SP ablation by cryoenergy is still associated with a higher rate of arrhythmia recurrence than is SP ablation by RF 2,3 ; long-term success, however, may improve with increasing experience, while the high safety profile is maintained. 6 As previous studies [12][13][14] reported higher long-term success rate with use of the 6-mm rather than the 4-mm-tip ablation catheter, we chose to use the former for all patients. In fact, a larger tip catheter is expected to create wider lesions, which are likely to be associated with less recurrences at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, several factors have been investigated. It has been shown that the use of 6-mm tip catheters relates to a lower recurrence rate compared to 4-mm tip [11,26]. On the other hand, the role of number and duration of cryoenergy applications on long-term outcome is controversial [15,27,28].…”
Section: Cooling Dynamicsmentioning
confidence: 99%
“…Previous studies focused on identifying factors that could affect acute and long-term efficacy, such as catheter tip size [11], electrophysiological markers of residual dual AV node physiology [11,12], duration and number of cryoenergy applications [13], but data are limited and sometimes controversial, and no strong predictor of cryoablation long-term efficacy has been identified [14][15][16]. The aim of this study is to evaluate the safety, acute and long-term efficacy of AVNRT cryoablation and to identify intra-procedural predictors of long-term efficacy, focusing on both electrophysiological parameters and cooling dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The use of 6-mm-tip cryoablation catheters seems to enhance short-term success rates. 10,11 The present study was designed as a multicenter prospective randomized trial to test the hypothesis that cryoablation for AVNRT is as effective (both short term and long term) as RFCA with a lower risk of permanent AV block.…”
Section: Clinical Perspective On P 2245mentioning
confidence: 99%